THE EFFECT OF BACKGROUND COLOR VARIATIONS ON THE LIGHT INTENSITY RECEIVED BY A LIGHT DEPENDENT RESISTOR (LDR) SENSOR - Fauziyyah, Rifa; Afrida, Juniar (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2025)
This study aims to analyze the effect of background color variation on the light intensityreceived by a Light Dependent Resistor (LDR) sensor. This study uses an experimentalmethod with a light source in the form of an LED lamp directed at white, black, red,green, blue, and yellow backgrounds. The sensor readings were obtained throughArduino Uno with the measurement results displayed in the form of Analog to DigitalConverter (ADC) values and converted into lux units. Data collection was carried outby repeating several times for each background color, then analyzed descriptively todetermine the relationship between color and sensor response. The results showed thatthe average ADC value was 1023, while the average light intensity was 139 lux,indicating that background color variation did not cause significant differences. Thesefindings suggest that other factors, such as LED light stability, distance betweencomponents, and the LDR's sensitivity limitations to certain wavelengths, had a moredominant influence on the results. The conclusion of this study is that background colorvariation does not significantly affect the LDR sensor response under the experimentalconditions used. This study contributes to physics education through an understandingof instrument limitations and the presentation of simple experiments that link opticaltheory with practical measurement results.